(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2021)
The Internet’s operation is steadily shifting from the "Internet of Computers" (IoC) to the "Internet of Things" (IoT). The issue that emerges is how to manage the massive amounts of data created with the considerably weaker available computer capability. Data science and artificial intelligence (AI) studies have been working to find a solution to this dilemma. As a result, IoT combined with AI has the potential to be a game changer. This isn’t only about saving money, doing clever things, decreasing effort and time, or following the latest trend. This is far more than just making life easier for people. Nevertheless, there are certain severe difficulties, such as security risks and ethical concerns, that will continue to plague IoT. The overall picture isn’t how exciting IoT with AI appears, but how ordinary people view it - as a blessing, a hardship, or a menace.